Analysis of Religious Culture in fostering Emotional Intelligence Students in Elementary School - Alamsyah, Elmania; Mu'alimin, Mu'alimin; Usriyah, Lailatul; Sutomo, Moh (ATTA`DIB, 2025)
This study aims to explore the application of religious culture in improving students' emotional intelligence at Ulul Albab Islamic Elementary School (SD) Jember. Qualitative methods were used in this study, involving observation and interview techniques as data collection instruments. A total of 13 informants, including religious teachers, class teachers, the principal and other school staff, were selected by purposive sampling. Data analysis used the Miles Huberman and Saldana model, considering data validity through triangulation of techniques and sources. The results showed that the implementation of a culture of religiosity at SDS Islam Ulul Albab Jember, such as morning tadarus, reciting and memorizing chapters of the Quran, reading istighfar and doing ablution when making mistakes, as well as the implementation of dhuha, dzuhur, asr prayers in congregation, contributed to improving students' emotional intelligence. These practices create a supportive and empowering learning environment, where students can develop better understanding and management of emotions. This research provides a deeper understanding of the importance of integrating religious culture in educational contexts to improve the quality of learning and holistic student development. The implications of this research provide guidance for educational institutions to adopt and strengthen religious cultural practices in an effort to improve students' emotional intelligence.